Achievements of the Cochrane Iran Associate Centre: Lessons Learned - Bita Mesgarpour; Sara Aghababa; Hamid Reza Baradaran; Payam Kabiri; Ali Kabir; Ahmad Sofi-Mahmudi; Ali Akbar Haghdoost (Kerman University of Medical Sciences, 2020)
Healthcare decision-making is a process that mainly depends on evidence and involves increasing numbers of stakeholders, including the consumers. Cochrane evidence responds to this challenge by identifying, appraising, integrating and synthesizing high-quality evidence. Recently, a collaborative effort has been initiated in Iran with Cochrane to establish a representative local entity. A variety of multifaceted interventions were conducted according to Cochrane's strategy to 2020, such as producing evidence, making Cochrane evidence accessible, advocating for evidence and building an effective and sustainable organization. In this report, the authors present the two and half year performance and achievements of Cochrane Iran based on a comprehensive and systematic approach. This case might be an example of health diplomacy, which is initiated by a successful international collaboration and proceed with recognizing the importance of adherence to the strategic action plans and goals.